2019
DOI: 10.1038/s41598-018-36490-1
|View full text |Cite
|
Sign up to set email alerts
|

POGLUT1, the putative effector gene driven by rs2293370 in primary biliary cholangitis susceptibility locus chromosome 3q13.33

Abstract: Primary biliary cholangitis (PBC) is a chronic and cholestatic autoimmune liver disease caused by the destruction of intrahepatic small bile ducts. Our previous genome-wide association study (GWAS) identified six susceptibility loci for PBC. Here, in order to further elucidate the genetic architecture of PBC, a GWAS was performed on an additional independent sample set, then a genome-wide meta-analysis with our previous GWAS was performed based on a whole-genome single nucleotide polymorphism (SNP) imputation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…In this study, we only showed that the xylosyl extension of O-Glc glycans may be involved in the regulation of Notch receptor trafficking using an overexpression system with room for improvement, and it should be further investigated how a xylosyl extension is involved in the above-mentioned, and possibly other, biological processes in vivo. Taken together, our findings suggest the importance of protein folding and O-glucosylation on multiple cysteine-rich EGF repeats of Notch receptors and provide insights into the pathological mechanisms in POGLUT1-related human diseases [51,52,[55][56][57].…”
Section: Discussionmentioning
confidence: 57%
“…In this study, we only showed that the xylosyl extension of O-Glc glycans may be involved in the regulation of Notch receptor trafficking using an overexpression system with room for improvement, and it should be further investigated how a xylosyl extension is involved in the above-mentioned, and possibly other, biological processes in vivo. Taken together, our findings suggest the importance of protein folding and O-glucosylation on multiple cysteine-rich EGF repeats of Notch receptors and provide insights into the pathological mechanisms in POGLUT1-related human diseases [51,52,[55][56][57].…”
Section: Discussionmentioning
confidence: 57%
“…5 Over the past decades, environmental factors have been extensively linked to the breakdown of immune tolerance in PBC as epidemiological and genetic studies, including genome-wide association studies (GWAS), have delineated key environmental factors and cellular pathways involved in the pathophysiology of the disease. [6][7][8][9][10][11] While it is already well accepted that the destruction of small bile ducts is mediated by a multilineage humoral and cellular response against BECs that involves both the innate and adaptive immune system, a major void in the bridge from the loss of tolerance to clinical pathology is the enigmatic observation that while mitochondria are found in all cells, only BECs are destroyed in PBC. Moreover, although the reasons why PBC selectively targets small bile ducts remain unclear, there is evidence to believe that BECs play an active role in PBC pathogenesis and that its destruction may depend on the heterogeneous response to the immune-mediated injury.…”
mentioning
confidence: 99%
“…DNA samples for GWASs were collected from 3,690 Japanese individuals (1,920 patients with PBC and 1,770 healthy controls) as described. ( 13,14,16 ) The diagnosis of PBC was performed according to the diagnostic criteria by the American Association for the Study of Liver Diseases. ( 2 ) The demographics and clinical features of these 1,920 patients are found in Supporting Table .Written informed consent was obtained from all participants.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Asian‐specific susceptibility regions for PBC ( CD58, CD28/CTLA4, IL21‐AS1, TNFSF15/TNFSF8, POU2AF1, IL16, IL21R, PRKCB, CSNK2A2/CCDC113, and ARID3A ) were identified in Japanese and Chinese populations. ( 13‐16 ) These results indicated that T‐cell activation pathways that produce interferon‐gamma (IFNG) (i.e., interleukin [IL]‐12 production in antigen‐presenting cells and subsequent IFNG production in T cells by IL‐12 and tumor necrosis factor [TNF] superfamily [TNFSF] 15 stimulation) and B‐cell differentiation and maturation pathways involving various transcription factors, which are encoded by SPIB, POU2AF1, IKZF3, and ARID3A , play important roles in the development of PBC. ( 17‐19 ) In addition, gene‐expression profiling microarray analysis using liver tissue samples or peripheral blood mononuclear cells indicated that many genes implicated in intrahepatic inflammation, fibrosis, and regeneration are up‐regulated in PBC.…”
mentioning
confidence: 99%